Design and Construction Analysis of a River Cruise Boat using an Electric Motor Drive - Aditya Djunaidi; Erifive Pranatal (National Research and Innovation Agency (BRIN Publishing), 2024)
Surabaya has many large rivers, so it has tourism potential if the management can utilize the river. Surabaya needs a ship that can accommodate river cruising activities to maximize the river's potential. Fiber-based boats are suitable for these activities because fiber materials tend to be durable, lightweight, and easily made. Therefore the boat was designed using fiberglass, which had the primary size; 10 meters long, 2.3 meters wide, 1.2 meters high, and 0.5 meters draft. The primary size allowed the boat to carry 11 passengers, including one helmsman, in one trip. The boat used an electric outboard engine with four horsepower that could make the boat travel at a speed of 4 knots, so the ship required 20 minutes to make a trip. The overall cost to make the boat amounted to Rp. 47.345.600.